Stability Indicating Development and Validation of Ultraviolet Spectrophotometric Methods for the Simultaneous Estimation of Bromhexine and Cephalexin in their Combined Dosage Form - Kumar, Dr. K. Kiran (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this study is to develop two simple, rapid, accurate, economical validated spectrophotometric for simultaneous estimation of bromhexine and cephalexin in bulk and dosage form. Materials and Methods: The Method-I is first derivative spectrophotometric and Method-II is the simultaneous equation method. Both the methods were employed for the analysis of drugs bromhexine and cephalexin using methanol and ammonium hydrogen phosphate (pH 7.7) in the ratio of 60:40 as a diluent. Results and Discussions: Both the methods are used for the simultaneous determination of bromhexine and cephalexin at 2155 nm and 266.5 nm, respectively, over the concentration range of 0.2–1.2 μg/ml and 12.5–75 μg/ml with the correlation coefficient (r2) 0.9996 and 0.9994. Conclusions: The recovery studies confirmed the accuracy of proposed method and low-value standard deviation confirmed precession of method. The method is validated as per the International Council for Harmonization guidelines.